Role of boron and its interaction with other elements in plants - Vera-Maldonado, Peter; Aquea, Felipe; Reyes-Díaz, Marjorie; Cárcamo-Fincheira, Paz; Soto-Cerda, Braulio; Nunes-Nesi, Adriano; Inostroza-Blancheteau, Claudio (Frontiers in Plant Science, 2024)
Boron (B) is an essential microelement for plants, and its deficiency can lead to impaired development and function. Around 50% of arable land in the world is acidic, and low pH in the soil solution decreases availability of several essential mineral elements, including B, magnesium (Mg), calcium (Ca), and potassium (K). Plants take up soil B in the form of boric acid (H3BO3) in acidic soil or tetrahydroxy borate [B(OH)4] -at neutral or alkaline pH. Boron can participate directly or indirectly in plant metabolism, including in the synthesis of the cell wall and plasma membrane, in carbohydrate and protein metabolism, and in the formation of ribonucleic acid (RNA). In addition, B interacts with other nutrients such as nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), zinc (Zn), manganese (Mn), and iron (Fe), as well as with beneficial elements like silicon (Si) and toxic element as aluminum (Al), and cadmium (Cd). Many studies show the importance of B nutrition when plants are in deficiency or when subjected to toxic elements, mitigating the negative effects. The role of B and its importance in the cell wall is now well understood. However, little is known at the biological level and its interactions in the plant cell. In addition, B interacts with other nutrients such as Ca, nitrogen (N), phosphorus (P), K, and zinc (Zn). In this review, we discuss the mechanisms of B uptake, absorptiontranslocation, and accumulation and its interactions with other elements, and how it contributes to the adaptation of plants to different environmental conditions. We also discuss potential B-mediated networks at the physiological and molecular levels involved in plant growth and development. However, more research will be needed to address the gaps that are not yet fully understood.